Perception of Education and Industry Leaders on Micro-Credentials and their Potential in Higher Education - Mohammad Santally; Yousra Banoor Rajabalee; Dorothy Cooshna-Naik; Wolfgang Greller (Journal of Learning for Development)
Micro-credentials are certifications that evaluate knowledge and skills acquired through specific learning experiences. This research explores the perceptions of education and industry leaders in Mauritius regarding recognition, ease of application, and value of micro-credentials in higher education. Interviews were conducted with 10 education and four industry leaders. The findings indicated that while the respondents lacked a deep understanding of micro-credentials as an educational model, they recognised the need to formalise its adoption within frameworks such as the National Qualification Framework (NQF) and a National Credit System. Additionally, there is a pressing need for reliable, competency-based assessments and structured pathways to map micro-credentials to university credits, leading to recognised qualifications. These insights from Mauritius can provide valuable lessons for other developing nations seeking to integrate micro-credentials into their higher education systems, helping to address skills gaps, promote lifelong learning, and create flexible educational pathways that align with local and global workforce demands.